Phase Coupling Between Baroreflex Oscillations of Blood Pressure and Heart Rate Changes in 21-Day Dry Immersion - Borovik, Anatoly S.; Orlova, Evgeniya A.; Tomilovskaya, Elena S.; Tarasova, Olga S.; Vinogradova, Olga L. (Frontiers in Physiology, 2020)
Introduction: Dry immersion (DI) is widely used ground-based model which reproduce effects of microgravity on the cardiovascular system and, therefore, can be used to study the mechanisms of post-flight orthostatic intolerance in cosmonauts. However, the effects of long-duration DI on cardiovascular system have not been studied yet. The aim of this work was to study the effects of 21-day DI on systemic hemodynamics and its baroreflex control at rest and during head-up tilt test (HUTT). Methods: Ten healthy young men were exposed to DI for 21 days. The day before, on 7th, 14th and 19th day of DI, as well as on the 1st and 5th days of recovery they performed HUTT: 15 min in supine position and then 15 min of orthostasis (60°). During the test, ECG, arterial pressure, stroke volume and respiration rate were recorded. Phase synchronization index (PSI) of beat-to-beat mean arterial pressure (MAP) and heart rate (HR) in the frequency band of baroreflex waves ( 0.1 Hz) was used as a quantitative measure of baroreflex activity. Results: During DI, strong tachycardia and the reduction of stroke volume were observed both in supine position and during HUTT, these indicators did not recover on post-immersion day 5. In contrast, systolic arterial pressure and MAP decreased during HUTT on 14th day of DI, but then restored to pre-immersion values. Before DI and on day 5 of recovery, a transition from supine position to orthostasis was accompanied by an increase in PSI at the baroreflex frequency. However, PSI did not change in HUTT performed during DI and post-immersion day 1. The amplitude of MAP oscillations at this frequency were increased by HUTT in all measurements, while an increase of respective HR oscillations was absent during DI. Conclusion: 21-day DI drastically changed the hemodynamic response to HUTT, while its effect on blood pressure was reduced between days 14 and 19, which speaks in favor of the adaptation to the conditions of DI. The lack of increase in phase synchronization of baroreflex MAP and HR oscillations during HUTT indicates disorders of baroreflex cardiac control during DI.